A high-load porous hollow magnetic microsphere and its preparation method and application
By preparing high-load porous hollow magnetic microspheres, the problems of poor pore making effect and difficult to control morphology in the prior art are solved, high loading and high magnetic content are achieved, and their performance in applications such as immunodiagnosis, cell sorting and nucleic acid purification are improved.
Patent Information
- Application Number
- CN202411984136.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In the prior art, porous hollow microspheres have poor pore making effects and difficult to control morphology and size, which leads to insufficient loading and magnetic content in applications such as chemiluminescence immunodiagnosis, cell sorting, and nucleic acid purification.
Water-based polyurethane is prepared by isocyanate, polyethylene glycol and hydroxyethyl methacrylate, and mixed with styrene, porogenic agent and azobisisobutyronitrile. Hollow porous microspheres are formed by self-emulsification and self-polymerization reaction, followed by nitration treatment and magnetic metal ion deposition to prepare high-load porous hollow magnetic microspheres.
The high loading and high magnetic content of porous hollow magnetic microspheres are achieved, and their performance in chemiluminescence immunodiagnosis, cell sorting, nucleic acid purification and other applications are improved. The cleaning of magnetic microspheres is simple and not easy to agglomerate.
Smart Images

Figure CN119391045B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biological protein separation, and in particular to a high-load porous hollow magnetic microsphere and a preparation method and application thereof. Background Art
[0002] Immunomagnetic beads are a type of spherical particles with magnetic properties and modified with functional groups on the surface. The functional groups on the particles can fix the immune ligands to the surface of the particles through covalent coupling or physical adsorption, and at the same time, they can be enriched in a targeted manner under the action of an external magnetic field, thereby achieving the purposes of efficient separation, purification, and detection. In recent years, they have been widely used in the fields of chemiluminescent immunoassay, cell sorting, and nucleic acid purification.
[0003] According to the different types of modification groups, chemiluminescent immunomagnetic beads are generally divided into carboxyl magnetic beads, tosyl magnetic beads, amino magnetic beads, etc. By coating antibodies, antigens, streptavidin and other immune ligands on the surface of magnetic beads, they can specifically bind to the antigens or antibodies to be tested in body fluids such as plasma and serum, thereby achieving the purpose of quantitative detection. However, if the composition of the components in serum is extremely complex, impurities other than the substances to be tested can easily interfere with the results and affect the accuracy. Therefore, the number of immune ligands that can be bound by immunomagnetic beads largely determines the sensitivity, linear range, signal value and accuracy of the test, while the specific surface area of the microspheres determines the upper limit of the binding capacity of the immune ligands.
[0004] On the other hand, the magnetic strength of chemiluminescent immunomagnetic beads will have a great impact on the separation efficiency, CV, and signal value during the application process, while superparamagnetic immunomagnetic beads are a basic requirement for performance parameters. Non-superparamagnetic magnetic microspheres are prone to microsphere aggregation due to residual magnetism, which has a great impact on test precision and repeatability. Traditional method models mainly include embedding method, in-situ method and monomer polymerization method. The embedding method is to dissolve the polymer in a solution containing magnetic ultrafine particles, and then add a large amount of precipitant, and precipitate the polymer substance on the surface of the magnetic particles through cross-linking, flocculation, atomization, deposition, evaporation and other means to form composite microspheres with core-shell structure. The polymer substance and the magnetic particles are mainly combined by van der Waals force, hydrogen bond, chelation or covalent bond. The monomer polymerization method is the most studied and widely used preparation method. The monomer polymerization method is a method for preparing magnetic polymer microspheres by adding surfactants, stabilizers, initiators, etc. according to different polymerization methods in the presence of organic monomers and magnetic particles. Commonly used methods mainly include emulsion polymerization, (micro) suspension polymerization, dispersion polymerization and active polymerization. Although the embedding method and monomer polymerization method can achieve high magnetic response performance under the condition of ensuring superparamagnetism, they have disadvantages such as uneven distribution of magnetic particles and poor dispersibility. The in-situ method is a method for preparing dispersed structure magnetic polymer composite microspheres. First, porous polymer microspheres are prepared, and then sulfonation or nitration treatment is performed to make the porous polymer microspheres have affinity with magnetic metal ions such as iron, manganese, and cobalt. Then, iron salts are added to the prepared microspheres, and the magnetic metal ions are oxidized and precipitated under alkaline conditions, so that magnetic particles are generated in the pores of the polymer microspheres, and finally magnetic composite microspheres are obtained. However, the in-situ method is limited by the specific surface area of the polymer microspheres and has the disadvantage of low magnetic loading.
[0005] Therefore, it is necessary to provide a magnetic microsphere with high macromolecular loading and high magnetic content and a preparation method thereof. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a high-load porous hollow magnetic microsphere and a preparation method and application thereof, so as to overcome the problems of poor pore making effect and difficult control of morphology and size in the preparation of porous hollow microspheres in the prior art, and to increase the loading capacity and magnetic content of the porous hollow magnetic microspheres coupled with macromolecules, so as to facilitate their application in chemiluminescent immunoassay cell sorting and nucleic acid purification.
[0007] The specific technical solutions are as follows:
[0008] The first aspect of the present invention provides a method for preparing porous hollow magnetic microspheres, comprising the following steps:
[0009] 1) Isocyanate and polyethylene glycol react under the action of a catalyst to obtain a prepolymer; then hydroxyethyl methacrylate is added to react to obtain a waterborne polyurethane;
[0010] 2) mixing the waterborne polyurethane, styrene, porogen and azobisisobutyronitrile to obtain an organic phase; adding water to the organic phase, reacting, separating and drying to obtain porous hollow microspheres;
[0011] 3) the porous hollow microspheres are nitrated in a mixture of nitric acid and sulfuric acid to obtain porous hollow nitrated microspheres;
[0012] 4) The porous hollow nitrated microspheres and the iron salt solution react under the action of ammonia water to obtain porous hollow magnetic microspheres.
[0013] The present invention prepares a nonionic waterborne polyurethane (WPU) with double bonds and PEG blocks by using isocyanate, polyethylene glycol and hydroxyethyl methacrylate. The nonionic waterborne polyurethane can use itself as an emulsifier and a polymerization monomer to obtain hollow porous microspheres through a self-emulsification and self-polymerization reaction.
[0014] Preferably, in 1), the isocyanate is selected from one or more of isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate and hexamethylene diisocyanate. In one embodiment, it is isophorone diisocyanate (IPDI).
[0015] Preferably, in 1), the molecular weight of the polyethylene glycol is 2000-5000, or 2000-4000, or 3000-5000. In a certain example, it is 2000 or 5000. The present application studies the molecular weight of polyethylene glycol and finds that the particle size of the hollow porous microspheres formed with the increase of the molecular weight of polyethylene glycol shows an increasing trend. When the molecular weight of polyethylene glycol is 2000, the particle size of the hollow porous microspheres is above 1 μm; when the molecular weight of polyethylene glycol is 5000, the particle size of the hollow porous microspheres is about 3 μm; and when the molecular weight of polyethylene glycol is 1000, the particle size of the hollow porous microspheres is about 0.8 μm or less; when the molecular weight of polyethylene glycol is 200, the particle size of the hollow porous microspheres is about 0.6 μm.
[0016] Preferably, in 1), the mass ratio of the polyethylene glycol to the isocyanate is (1-10):1, or (1-4.4):1, or (4.0-10):1. In one embodiment, it is 2:0.44.
[0017] Preferably, in 1), the molar ratio of the isocyanate group in the isocyanate to the hydroxyl group in the hydroxyethyl methacrylate is 1 to 3. In the present application, hydroxyethyl methacrylate (HEMA) can introduce double bonds and hydroxyl functional groups at the end of the polyurethane chain, and the double bonds in HEMA can cross-link with the polymerized monomers during the polymerization process to form a network structure. In the present application, the molar ratio of the isocyanate group in the isocyanate to the hydroxyl group in the hydroxyethyl methacrylate (ie, the R value) should not be too high or too low. If it is too high, the proportion of isocyanate will be too high, the cost will increase significantly, and it is not suitable for large-scale production; if the molar ratio is less than 1, the molecular weight of the prepolymer obtained by the reaction will be too low, and only dimers or trimers can be formed, not polymers, and microspheres cannot be formed, which will affect the performance of the microspheres.
[0018] Preferably, in 1), the catalyst is dibutyltin dilaurate (DBTDL).
[0019] Preferably, in 1), the mass ratio of the cyanate ester to the catalyst is (10-30):1, or (0.05-5):1, or (4-8):1. In one embodiment, it is 1:22.
[0020] Preferably, in 1), the temperature of the catalytic reaction is 60-80°C, or 60-75°C, or 70-90°C. In one embodiment, it is 75°C.
[0021] Preferably, in 1), the catalytic reaction time is 2 to 48 hours, or 1 to 24 hours, or 20 to 48 hours. In one embodiment, it is 4 hours.
[0022] Preferably, in 1), the reaction temperature is 60-80°C, or 60-75°C, or 70-90°C. In one embodiment, it is 75°C.
[0023] Preferably, in 1), the reaction time is 2 to 48 hours, or 1 to 24 hours, or 20 to 48 hours. In one embodiment, it is 6 hours.
[0024] Specifically, in one example, the following steps are included: 2 g PEG2000 and 0.02 g DBTDL are dispersed in 10 g toluene, 0.44 g IPDI is added and reacted at 75°C for 4 hours to obtain a prepolymer; then 0.26 g HEMA is added and reacted at 75°C for 6 hours to obtain a waterborne polyurethane.
[0025] Preferably, in 2), the solid content of the aqueous polyurethane is 20-30%. The aqueous polyurethane is a solvent solution of aqueous polyurethane, and the solvent is selected from toluene. Unless otherwise specified, aqueous polyurethane refers to the aqueous polyurethane obtained in step 1), not the solvent solution of aqueous polyurethane. The present application found that the solid content of aqueous polyurethane should not be too high or too low. If it is too high, the proportion of polyurethane components will be too high, the viscosity of the solution system will be too large, the phase transition resistance will increase, the difficulty of balling will increase or solid microspheres will be formed; if it is too low, the shell layer of the porous hollow microspheres will be too thin and insufficiently rigid, causing structural collapse.
[0026] Preferably, in 2), the porogen is selected from one or more of toluene, cyclohexane, isopropanol and N,N-dimethylformamide, preferably toluene.
[0027] Preferably, in 2), the mass ratio of the porogen to the aqueous polyurethane is (0.05-8):1, or (0.05-5):1, or (4-8):1. In one embodiment, it is 4:1.
[0028] Preferably, in 2), the mass ratio of styrene to waterborne polyurethane is (0.05-5):1, or (0.05-2):1, or (1-5):1. In one embodiment, it is 0.5:1.
[0029] Preferably, in 2), the mass ratio of azobisisobutyronitrile (AIBN) to waterborne polyurethane is (0.001-0.2):1, or (0.001-0.12):1, or (0.08-0.2):1. In one embodiment, it is 0.02:1.
[0030] Preferably, in 2), the reaction temperature is 60-90°C, or 60-75°C, or 70-90°C. In one embodiment, it is 70°C.
[0031] Preferably, in 2), the reaction time is 1 to 48 hours, or 1 to 24 hours, or 20 to 48 hours. In one embodiment, it is 16 hours.
[0032] Specifically, in a certain example, the following steps are included: 1 g of waterborne polyurethane, 0.5 g of styrene, 4 g of toluene and 0.02 g of AIBN are mixed at a stirrer speed of 1500 rpm to form an organic phase; then 10 g of pure water is added to the organic phase, stirred for 30 minutes, and reacted at 70°C and a speed of 200 rpm for 16 hours. After the reaction is completed, it also includes suction filtration to obtain a white solid, which is washed with anhydrous ethanol and suction filtered, and after repeating 3 times, it is placed in a vacuum drying oven at 120°C and dried for 48 hours to obtain porous hollow microspheres.
[0033] Preferably, in 3), the weight ratio of the porous hollow microspheres to the mixed solution is 1 g:(7-35) g, or can be, or can be. In a certain embodiment, it is 1:24.
[0034] Preferably, in 3), the mass ratio of sulfuric acid to nitric acid is (1-10):1, or (1-5):1, or (4-10):1. In one embodiment, it is 4.8:1.
[0035] Preferably, in 3), the temperature of the nitrification treatment is 20-60°C, or 20-42°C, or 40-60°C. In one embodiment, it is 30°C.
[0036] Preferably, in 3), the nitrification treatment time is 1 to 24 hours, or 1 to 24 hours, or 20 to 48 hours. In one embodiment, it is 2 hours.
[0037] Specifically, in a certain example, the following steps are included: a mixed solution of 25 g of 95% sulfuric acid and 7.5 g of 65% nitric acid is cooled to 10°C, and then 1 g of porous hollow microspheres is added, and then the temperature is raised to 30°C for reaction for 2 hours to obtain the nitrated porous hollow microspheres. After the reaction, the steps include cooling, filtering, ethanol washing, water washing, and drying.
[0038] Preferably, in 4), the mass ratio of the iron salt in the iron salt solution to the porous hollow nitrated microspheres is (3-15):1, or (3-10):1, or (6-15):1. In one embodiment, it is 10:1.
[0039] Preferably, in 4), the iron salt is selected from ferrous sulfate. In one embodiment, it is FeSO4·7H2O.
[0040] Preferably, in 4), the mass concentration of the ammonia water is 1-35wt%, or 1-20wt%, or 15-35wt%. In one embodiment, it is 20wt%.
[0041] Preferably, in 4), the reaction temperature is 40-100°C, or 40-70°C, or 60-100°C. In one embodiment, it is 60°C.
[0042] Preferably, in 4), the reaction time is 1 to 24 hours, or 1 to 24 hours, or 20 to 48 hours. In one embodiment, it is 4 hours.
[0043] Preferably, in 4), the reaction further comprises adding manganese sulfate.
[0044] Specifically, in one example, the method includes the following steps: 1 g of porous hollow nitrated microspheres are dispersed in 10 g of water, and reacted with 10 g of FeSO4·7H2O, 0.02 g of MnSO4·H2O and 10 mL of 25% ammonia water at 60° C. for 4 hours to obtain porous hollow magnetic microspheres. After the reaction, magnetic separation and washing may also be performed.
[0045] Preferably, the method further comprises coating the porous hollow magnetic microspheres, wherein the coating comprises the following steps: a first reaction is carried out between the porous hollow magnetic microspheres, dibutyltin dilaurate and isophorone diisocyanate, and then hydroxyethyl methacrylate is added to carry out a second reaction to obtain coated microspheres.
[0046] More preferably, the mass ratio of the porous hollow magnetic microspheres to the dibutyltin dilaurate (DBTDL) is 1:(0.005-0.1), or 1:(0.005-0.05), or 1:(0.04-0.1). In one embodiment, it is 1:0.01.
[0047] More preferably, the mass ratio of the porous hollow magnetic microspheres to isophorone diisocyanate (IPDI) is 1:(0.2-5), or 1:(0.2-3, or 1:(2-5). In one embodiment, it is 1:1.
[0048] More preferably, the mass ratio of the porous hollow magnetic microspheres to hydroxyethyl methacrylate (HEMA) is 1:(0.1-1), or 1:(0.1-0.6), or 1:(0.5-1). In one embodiment, it is 1:0.26.
[0049] More preferably, the temperature of the first reaction is 40-100°C, or 40-70°C, or 60-100°C. In one embodiment, it is 75°C.
[0050] More preferably, the second reaction time is 1 to 48 hours, or 1 to 24 hours, or 20 to 48 hours. In one embodiment, it is 4 hours.
[0051] More preferably, the temperature of the second reaction is 40-100°C, or 40-70°C, or 60-100°C. In one embodiment, it is 75°C.
[0052] More preferably, the first reaction time is 1 to 48 hours, or 1 to 24 hours, or 20 to 48 hours. In one embodiment, it is 6 hours.
[0053] Specifically, in a certain example, the coating comprises the following steps: 1 g of porous hollow magnetic microspheres is dispersed in 10 g of acetone, reacted with 0.01 g of DBTDL and 1 g of IPDI at 75° C. for 4 h, 0.26 g of HEMA is added and reacted at 75° C. for 6 h, magnetic separation is performed, and washing is performed to obtain coated microspheres. During the washing, the detergent used is ethanol or water.
[0054] More preferably, the method further comprises performing carboxyl modification on the coated spheres, wherein the carboxyl modification comprises the following steps: reacting the coated spheres, azobisisobutyronitrile and acrylic acid.
[0055] More preferably, the mass ratio of the coated ball to azobisisobutyronitrile (AIBN) is 1:(0.01-0.5), or 1:(0.01-0.3), or 1:(0.2-0.5). In one embodiment, it is 1:0.04.
[0056] More preferably, the mass ratio of the coated ball to the acrylic acid is 1:(1-3), or 1:(1-1.8), or 1:(1.5-3). In one embodiment, it is 1:2.
[0057] More preferably, the reaction temperature is 40-100°C, or 40-60°C, or 50-100°C. In one embodiment, it is 70°C.
[0058] More preferably, the reaction time is 1 to 48 hours, or 1 to 24 hours, or 20 to 48 hours. In one embodiment, it is 16 hours.
[0059] Further preferably, the reaction is carried out in a protective atmosphere selected from nitrogen.
[0060] In a specific example, the carboxyl modification includes the following steps: 1 g of the coated spheres are dispersed in 10 g of ethanol, reacted with 0.04 g of AIBN and 2 g of acrylic acid at 70° C. for 16 h, and washed. During the washing, the washing agent used is ethanol or water.
[0061] The second aspect of the present invention provides porous hollow magnetic microspheres obtained by the preparation method as described above.
[0062] The third aspect of the present invention provides use of the porous hollow magnetic microspheres as described above for chemiluminescent immunodiagnosis, cell sorting or nucleic acid purification.
[0063] The porous hollow magnetic microspheres of the present invention have the advantages of large specific surface area, high magnetic content, and large macromolecular loading capacity, and can be used as solid phase carriers for immunoassays, and as immunomagnetic beads for chemiluminescent immunodiagnosis, cell sorting, or nucleic acid purification.
[0064] Compared with the prior art, the present invention has the following beneficial effects:
[0065] 1) The porous hollow magnetic microspheres obtained by the present invention can achieve a higher loading capacity by coupling antibodies, proteins and other macromolecules.
[0066] 2) The preparation method of the present invention realizes the magnetization of the shell interior, pore interior and shell surface of the porous hollow microspheres by an in-situ method; at the same particle size, by the in-situ method, while ensuring the superparamagnetic performance, it has a magnetic response performance close to that of the monomer polymerization method.
[0067] 3) The porous solid model microspheres used in the traditional in-situ method have a low upper limit for magnetic content. For example, for 1μm magnetic beads, the upper limit for magnetic content can only reach about 50%. At this time, the residual magnetism is very serious, so it is easy to agglomerate and have more residual magnetism. The porous hollow magnetic microspheres of the present application are easy to clean, have a high upper limit for magnetic content, are not easy to agglomerate, and have no residual magnetism. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 The electron microscope images of the porous hollow microspheres and the magnetized porous hollow magnetic microspheres in Example 1 of the present application are shown in Figure 1. A is a scanning electron microscope image (0.5 μm), and B is a scanning electron microscope image at a magnification (100 nm).
[0069] Figure 2 This is a graph showing the magnetic content dispersion results of the porous hollow magnetic microspheres of Example 1 of the present application. Among them, M4 represents a feed ratio of 3g:1g of FeSO4•7H2O / nitrification ball; M5 represents a feed ratio of 6g:1g of FeSO4•7H2O / nitrification ball; M6 represents a feed ratio of 10g:1g of FeSO4•7H2O / nitrification ball; and M7 represents a feed ratio of 15g:1g of FeSO4•7H2O / nitrification ball.
[0070] Figure 3 This is a result diagram of the magnetic response time of the porous hollow magnetic microspheres of Example 1 of the present application. Among them, 3*Fe represents the feed ratio of FeSO4•7H2O / nitrified porous hollow microspheres of 3g:1g; 6*Fe represents the feed ratio of FeSO4•7H2O / nitrified porous hollow microspheres of 6g:1g; 10*Fe represents the feed ratio of FeSO4•7H2O / nitrified porous hollow microspheres of 10g:1g; 15*Fe represents the feed ratio of FeSO4•7H2O / nitrified porous hollow microspheres of 15g:1g.
[0071] Figure 4This is a graph showing the magnetic content dispersion results of the porous non-hollow magnetic microspheres of Comparative Example 1 of the present application. Among them, M1 represents the feed ratio of FeSO4•7H2O / nitrated porous non-hollow microspheres of 3g:1g; M2 represents the feed ratio of FeSO4•7H2O / nitrated porous non-hollow microspheres of 6g:1g; M3 represents the feed ratio of FeSO4•7H2O / nitrated porous non-hollow microspheres of 10g:1g.
[0072] Figure 5 This is a result diagram of the magnetic response time of the porous non-hollow magnetic microspheres of Comparative Example 1 of the present application. Among them, 3*Fe represents the feed ratio of FeSO4•7H2O / nitrated porous non-hollow microspheres of 3g:1g; 6*Fe represents the feed ratio of FeSO4•7H2O / nitrated porous non-hollow microspheres of 6g:1g; 10*Fe represents the feed ratio of FeSO4•7H2O / nitrated porous non-hollow microspheres of 10g:1g. DETAILED DESCRIPTION
[0073] The present invention will be further described below in conjunction with specific embodiments. The following are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto.
[0074] Example 1
[0075] 1.1 Preparation of porous hollow microspheres
[0076] 1) Take 2 g of polyethylene glycol PEG5000 and 0.02 g of catalyst dibutyltin dilaurate (DBTDL), dissolve them in 10 g of toluene, add them to a three-necked flask with a mechanical stirrer, set the stirrer speed to 250 rpm, pass nitrogen for 30 minutes, set the temperature to 75°C, add 0.44 g of isophorone diisocyanate (IPDI), react at 75°C for 4 hours to obtain a prepolymer; then add 0.26 g of hydroxyethyl methacrylate (HEMA), react at 75°C for 6 hours, after the end, measure the solid content, dilute with toluene solution to a solid content of 20%, obtain a toluene solution of WPU, and save it for later use.
[0077] 2) Take the toluene solution containing 1 g of WPU obtained in step 1), add 0.5 g of styrene and 4 g of toluene, mix well, add to a three-necked flask weighing 0.02 g of azobisisobutyronitrile (AIBN), set the stirrer speed to 1500 rpm, and after passing nitrogen for 30 minutes, obtain an organic phase; then quickly add 10 g of pure water to the organic phase, stir for 30 minutes, and after the end, set the temperature to 70°C, adjust the speed to 200 rpm, and react for 16 hours.
[0078] 3) After the reaction is completed, filter to obtain a white solid, wash with anhydrous ethanol and filter, repeat three times, put it into a vacuum drying oven at 120°C, dry it for 48 hours, and obtain porous hollow microspheres (abbreviated as WPUMs), which are stored for later use.
[0079] 1.2 Preparation of nitrated porous hollow microspheres
[0080] Cool the mixture of 25 g 95% sulfuric acid and 7.5 g 65% nitric acid to 10°C, then add 1 g of WPUMs obtained in step 1.1. Raise the temperature to 30°C and stir at 250 rpm for 2 hours. Then, add 150 g of ice water. Filter, wash with ethanol 3 times, then wash with pure water 3 times, and dry to obtain a yellow solid powder, which is porous hollow nitrated microspheres (nitrated microspheres).
[0081] 1.3 Preparation of porous hollow magnetic microspheres
[0082] According to the feed ratio of porous hollow nitrified microspheres (nitrified balls) and FeSO4•7H2O in Table 1, take the porous hollow nitrified microspheres obtained in step 1.2, disperse them with 10 g pure water, add them to a three-necked flask filled with FeSO4•7H2O and 0.02 g MnSO4•H2O, start stirring, and pass nitrogen for 30 minutes at a speed of 250 rpm. Raise the temperature to 60°C, add 10 mL of 25% ammonia water, react at 60°C for 4 hours, and magnetize to obtain porous hollow magnetic microspheres. Magnetic separation, wash and disperse with pure water to obtain a dispersion of porous hollow magnetic microspheres. Determine the solid content of the dispersion and save it for later use. The scanning electron microscope image of the porous hollow magnetic microspheres is shown in Figure 1 A and B.
[0083] 1.4 Wrapping
[0084] Take 1 g of the porous hollow magnetic microspheres obtained in step 1.3, separate them by magnetic separation, wash them with acetone three times, then disperse them with 10 g of acetone, add them to a three-necked flask containing 0.01 g of dibutyltin dilaurate (DBTDL) and 1 g of isophorone diisocyanate (IPDI), set the stirrer speed to 250 rpm, pass nitrogen for 30 minutes, raise the temperature to 75°C, react at 75°C for 4 hours, add 0.26 g of hydroxyethyl methacrylate (HEMA), react at 75°C for 6 hours, after the end, separate them by magnetic separation, wash them with ethanol three times, wash them with pure water three times, disperse them with pure water, obtain coated balls, determine the solid content, and store them for later use. The solid content is used for the feed ratio of coated balls and acrylic acid in step 1.5.
[0085] 1.5 Carboxyl modification
[0086] Take 1 g of the coated spheres obtained in step 1.4, separate them by magnetic separation, wash them with ethanol three times, and then disperse them with 10 g of ethanol, add them to a three-necked flask containing 0.04 g of initiator azobisisobutyronitrile (AIBN) and 2 g of acrylic acid, set the stirrer speed to 250 rpm, pass nitrogen for 30 minutes, raise the temperature to 70°C, react at 70°C for 16 hours, and after completion, wash them with ethanol three times, wash them with pure water three times, disperse them with pure water, measure the solid content, obtain carboxyl-modified magnetic microspheres, and store them for later use. The solid content is used to calculate the coupling ratio with streptavidin in step 1.6.
[0087] 1.6 Immobilization of streptavidin
[0088] (1) Take 10 mg of the carboxyl-modified magnetic microspheres obtained in step 1.5, perform magnetic separation, remove the supernatant, and wash three times with MES at pH 6.0. Add 1 mg of streptavidin dissolved in 900 uL of MES at pH 6.0 to the carboxyl-modified magnetic beads washed three times with MES to obtain a mixed dispersion of magnetic beads and streptavidin.
[0089] (2) Incubate the mixed dispersion of carboxyl-modified magnetic beads and streptavidin at room temperature for 30 minutes using a mixing device.
[0090] (3) Weigh 1 mg of EDC, dissolve it in 100 uL pH 6.0 MES, add it to the mixed dispersion after incubation in step (2), and react at room temperature for 5 hours.
[0091] (4) Magnetic separation: remove the supernatant and wash three times with pH 7.4 phosphate buffer containing 0.01% (W / V) Tween-20 to remove excess EDC and streptavidin. Finally, disperse the microspheres with 1 mL of pH 7.4 phosphate buffer containing 0.01% (W / V) Tween-20 to obtain porous hollow immunomagnetic microspheres. Store the microspheres at 2-8°C for future use.
[0092] The porous hollow magnetic microspheres obtained in step 1.3 were tested for magnetic content and magnetic response time. The details are as follows:
[0093] Magnetic content calculation: The solid content data of the dispersion after magnetization (C 固含量 ), the total mass of the dispersion after magnetization (m a ) and mass of nitrated porous hollow microspheres (m b ), the magnetic content is calculated according to the following formula, accurate to 0.01%.
[0094]
[0095] Among them, the solid content data (C 固含量) is the solid content of the dispersion in step 1.3, %; the total mass of the dispersion after magnetization (m a ) is the total mass of the dispersion in step 1.3, g; the mass of the nitrifying ball (m b ) is the feeding amount of porous hollow nitration microspheres in step 1.3, g.
[0096] Magnetic response time test: The magnetic response time (t 50 ) for testing.
[0097] Magnetic response time (t 50 ) refers to the time required for the magnetic beads to completely aggregate from a uniformly dispersed state under the action of an external magnetic field. The shorter the magnetic response time, the shorter the time required from a uniformly dispersed state to complete aggregation, which means that the magnetic beads are more likely to aggregate and have poor dispersion.
[0098] Solid content test: ① Take a clean and dry glass weighing bottle and record its mass to an accuracy of 0.001g, recorded as m1. Peel the analytical balance. ② Weigh the dispersion of porous hollow magnetic microspheres, place it in a weighed glass weighing bottle, record the weight to an accuracy of 0.001g, recorded as m2. ③ Place the glass bottle containing the dispersion of porous hollow magnetic microspheres in a blast drying oven at a temperature of 120°C and heat it for 4 hours. ④ After the test time is up, take out the glass bottle, put it in a dryer and cool it to room temperature, weigh its mass to an accuracy of 0.001g, recorded as m3. ⑤ Calculate the solid content according to the following formula to an accuracy of 0.01%.
[0099] C 固含量 = (m3-m1) / m2*100%
[0100] The test results of magnetic content are shown in Table 1. Figure 2 ; The detection results of magnetic response are shown in Table 1 and Figure 3 .
[0101] Figure 2 The figure is the result of magnetic content dispersion of porous hollow magnetic microspheres in this embodiment. Among them, M4 represents the feed ratio of FeSO4•7H2O / nitrification ball 3g:1g; M5 represents the feed ratio of FeSO4•7H2O / nitrification ball 6g:1g; M6 represents the feed ratio of FeSO4•7H2O / nitrification ball 10g:1g; M7 represents the feed ratio of FeSO4•7H2O / nitrification ball 15g:1g.
[0102] Figure 3The magnetic response time result diagram of the porous hollow magnetic microspheres in this embodiment. Among them, 3*Fe represents the feed ratio of FeSO4•7H2O / nitrified porous hollow microspheres of 3g:1g; 6*Fe represents the feed ratio of FeSO4•7H2O / nitrified porous hollow microspheres of 6g:1g; 10*Fe represents the feed ratio of FeSO4•7H2O / nitrified porous hollow microspheres of 10g:1g; 15*Fe represents the feed ratio of FeSO4•7H2O / nitrified porous hollow microspheres of 15g:1g.
[0103] Table 1 Effects of different feed ratios on magnetic content, magnetic response time and dispersibility of porous hollow magnetic microspheres
[0104]
[0105] From Table 1, Figure 2 as well as Figure 3 It can be seen that with the increase of the feed ratio of FeSO4•7H2O and nitrifying balls, the magnetic content increases significantly, and the increase gradually tends to the upper limit at a feed ratio of 15 times, with the magnetic content as high as 95.2%. The magnetic response time also shortens significantly with the increase of the magnetic content, and also tends to the upper limit at a feed ratio of 15 times, t 50 The time of the magnetic beads was 17.6 s. Under an optical microscope, it can be observed that only a slight linear arrangement occurs when the feed ratio is 15 times. The linear arrangement refers to the magnetic beads gathering together in a linear pattern. Therefore, it is shown that when the feed ratio of FeSO4•7H2O and nitrification balls is (3-15) g:1g, the magnetic content is 44.8-95.2%, and the magnetic beads are not easy to agglomerate. Exceeding this range will lead to aggregation or a decrease in magnetic content. When the feed ratio of FeSO4•7H2O and nitrification balls is 15g:1g, there is residual magnetism, which causes the porous hollow magnetic microspheres to have a slight linear arrangement.
[0106] Comparative Example 1
[0107] Compared with Example 1, the difference between this Comparative Example 1 is that: in step 1.1, the aqueous polyurethane is diluted with toluene to a solid content of 40%, and the rest is the same as Example 1 to obtain porous non-hollow magnetic microspheres; then, the coating, carboxyl modification and streptavidin fixation are continued to obtain porous non-hollow immunomagnetic microspheres.
[0108] The magnetic content of the porous non-hollow magnetic microspheres obtained after magnetization was tested. Figure 4 and Table 2; and perform magnetic response time detection, see Figure 5 and Table 2.
[0109] Figure 4The figure is the result of magnetic content dispersion of porous non-hollow magnetic microspheres in comparative example 1. Among them, M1 represents the feed ratio of FeSO4•7H2O / nitrated porous non-hollow microspheres 3g:1g; M2 represents the feed ratio of FeSO4•7H2O / nitrated porous non-hollow microspheres 6g:1g; M3 represents the feed ratio of FeSO4•7H2O / nitrated porous non-hollow microspheres 10g:1g.
[0110] Figure 5 This is a result diagram of the magnetic response time of the porous non-hollow magnetic microspheres in this comparative example 1. Among them, 3*Fe represents the feed ratio of FeSO4•7H2O / nitrated porous non-hollow microspheres of 3g:1g; 6*Fe represents the feed ratio of FeSO4•7H2O / nitrated porous non-hollow microspheres of 6g:1g; 10*Fe represents the feed ratio of FeSO4•7H2O / nitrated porous non-hollow microspheres of 10g:1g.
[0111] Table 2 Effects of different feed ratios on magnetic content, magnetic response time and dispersibility of porous non-hollow magnetic microspheres
[0112]
[0113] From Table 2 and Figure 4 , 5 It can be seen that with the increase of the feed ratio of FeSO4•7H2O and nitrifying balls, the magnetic content increases accordingly, but the increase gradually tends to the upper limit at a feed ratio of 10 times, and the magnetic content is only 47%. The magnetic response time also shortens with the increase of the magnetic content, and also tends to the upper limit at a feed ratio of 10 times, t 50 The time is 77.9 s. Under an optical microscope, it can be observed that the wiring is serious and slight wiring has begun to appear at a 6-fold feed ratio.
[0114] The porous hollow magnetic microspheres M4-M7 (Table 1) in Example 1 were used to obtain porous hollow immunomagnetic microspheres (SA magnetic beads or magnetic beads), and the porous non-hollow magnetic microspheres M2-M3 (Table 2) in Comparative Example 1 were used to obtain porous non-hollow immunomagnetic microspheres (SA magnetic beads or magnetic beads), and the free biotin binding amount was tested, and the results are shown in Table 3; the thyroid stimulating hormone was tested, and the results are shown in Table 4. The detection method is as follows:
[0115] Test of free biotin binding amount: The free biotin binding amount of SA magnetic beads was quantified by the biotinylated fluorescein (B4F) method using the TECAN Infinite200Pro multifunctional microplate reader. The unit is pmol / mg. The formula is as follows.
[0116]
[0117] Where F0 is the fluorescence intensity of 10 nmol / ml B4F in PBS (excitation wavelength is 490 nm, emission wavelength is 525 nm), F1 is the fluorescence intensity of the supernatant solution after the magnetic beads to be tested reacted with 1 ml of 10 nmol / ml B4F in PBS at room temperature for 1 h (excitation wavelength is 490 nm, emission wavelength is 525 nm), m is the mass of magnetic beads in step 1.6.
[0118] Specific steps: Take 6 mg of the magnetic beads to be tested, take 3 mg each and add them to two 2 mL EP tubes, magnetically separate, remove the supernatant, add 1 mL of 50mM pH=7.4 PBS buffer, and shake well. Take one tube for solid-liquid separation, remove the supernatant, repeat 3 times, add 1 mL of 10nmol / ml B4F solution, shake well, wrap the outside of the EP tube with aluminum foil to completely avoid light, and react at room temperature for 2 hours on a rotary mixer. The other tube is not treated separately, the outside of the EP tube is wrapped with aluminum foil to completely avoid light, and react at room temperature for 2 hours on a rotary mixer as a control. After the reaction is completed, magnetic separation is performed, 200 μL of the supernatant is taken out, and added to a black 96-well ELISA plate at a volume of 200 μL / well, and the multifunctional ELISA reader is set to an excitation wavelength of 490 nm, an emission wavelength of 525 nm, and a Gain value of 50. Repeat the test twice, take the average value, and substitute the following formula into the calculation to obtain the biotin binding amount of the SA magnetic beads.
[0119] Detection of thyrotropin by magnetic bead double antibody sandwich method: 1) preparing a series of thyrotropin solutions with different concentration gradients, with a concentration range of 0-100 mIU / mL; 2) mixing different concentrations of biotin-mouse anti-thyrotropin solutions with pH=7.4 PBS buffer containing SA magnetic beads of Example 1 and Comparative Example 1, adding biotin-mouse anti-thyrotropin monoclonal antibody 1 (mAb1) and acridinium ester-mouse anti-thyrotropin monoclonal antibody 2 (mAb2) for oscillation incubation, then magnetically separating the products, washing the products with pH=7.4 PBS buffer, and redispersing them in pH=7.4 PBS buffer, adding hydrogen peroxide with a final concentration of 0.4-1.0 mM and hydrogen peroxide with a final concentration of 0.1-0.3 mM sodium hydroxide, and the chemiluminescence intensity of the immune complex was measured using a chemiluminescence immunoassay; the chemiluminescence intensity value of the SA magnetic beads after detecting different concentrations of thyrotropin was recorded as Y, the concentration of thyrotropin was recorded as X, and the chemiluminescence intensity was used as the vertical coordinate to prepare a standard curve, and fit the regression curve.
[0120] Table 3 Free biotin binding amount of porous hollow / porous non-hollow streptavidin magnetic beads with different magnetic contents
[0121]
[0122] It can be seen from Table 3 that the amount of free biotin bound by the porous hollow magnetic microspheres or magnetic beads in Example 1 is about 3 times that of Example 1, indicating that the porous hollow morphology in the porous hollow magnetic microspheres or magnetic beads of the present application not only has a significant advantage in increasing the magnetic content, but also has a higher upper limit in the capacity of loading proteins.
[0123] In Table 4 , TC1, TC2, TC3, TC4, TC5, TC6, and TC7 represent the concentrations of the antigen (thyrotropin), respectively, TC1 indicates an antigen concentration of 0 mIU / L, TC2 indicates an antigen concentration of 0.05 mIU / L, TC3 indicates an antigen concentration of 0.2 mIU / L, TC4 indicates an antigen concentration of 5.0 mIU / L, TC5 indicates an antigen concentration of 20 mIU / L, TC6 indicates an antigen concentration of 42 mIU / L, and TC7 indicates an antigen concentration of 85 mIU / L.
[0124] Table 4 Performance comparison of porous hollow / porous non-hollow streptavidin magnetic beads with different magnetic contents in the double antibody sandwich method
[0125]
[0126] As can be seen from Table 4, in the detection of thyroid stimulating hormone (TSH), the signal value of M4-SA and M7-SA is 3-4 times that of M2-SA, and the sensitivity represented by TC2 / TC1 is also increased by nearly 2 times, which also illustrates the natural advantage of the porous hollow morphology in the porous hollow magnetic microspheres or magnetic beads of the present application in chemiluminescent immunoassay.
Claims
1. A method for preparing porous hollow magnetic microspheres, characterized in that: The steps include: 1) Isocyanate and polyethylene glycol react under the action of a catalyst to obtain a prepolymer; then hydroxyethyl methacrylate is added to react to obtain a waterborne polyurethane; 2) mixing the waterborne polyurethane, styrene, porogen and azobisisobutyronitrile to obtain an organic phase; adding water to the organic phase, reacting, separating and drying to obtain porous hollow microspheres; 3) the porous hollow microspheres are nitrated in a mixture of nitric acid and sulfuric acid to obtain porous hollow nitrated microspheres; 4) the porous hollow nitrated microspheres and the iron salt solution react under the action of ammonia water to obtain porous hollow magnetic microspheres; 1), the molar ratio of the isocyanate group in the isocyanate to the hydroxyl group in the hydroxyethyl methacrylate is 1 to 3; 2), the solid content of the waterborne polyurethane is 20-30%.
2. The preparation method according to claim 1, characterized in that: 1), wherein the isocyanate is selected from one or more of isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate and hexamethylene diisocyanate; And / or, in 1), the molecular weight of the polyethylene glycol is 2000 to 5000; And / or, in 1), the mass ratio of the polyethylene glycol to the isocyanate is (1-10):1; And / or, in 1), the catalyst is dibutyltin dilaurate, and the mass ratio of the isocyanate to the catalyst is (10-30):1; And / or, in 1), the reaction temperature is 60-80°C; And / or, in 1), the reaction time is 2 to 48 hours.
3. The preparation method according to claim 1, characterized in that: 2), wherein the porogen is selected from one or more of toluene, cyclohexane, isopropanol and N,N-dimethylformamide; And / or, in 2), the mass ratio of the porogen to the aqueous polyurethane is (0.05-8):1; And / or, in 2), the mass ratio of styrene to waterborne polyurethane is (0.05-5):1; And / or, in 2), the mass ratio of azobisisobutyronitrile and waterborne polyurethane is (0.001-0.2): 1; And / or, in 2), the mixing temperature is 60-90°C.
4. The preparation method according to claim 1, characterized in that: 3), the mass ratio of the porous hollow microspheres to the mixed solution is 1:(7-35); And / or, in 3), the mass ratio of sulfuric acid to nitric acid is (1-10):1; And / or, in 3), the temperature of the nitrification treatment is 20 to 60°C; And / or, in 3), the nitrification treatment time is 1 to 24 hours.
5. The preparation method according to claim 1, characterized in that: 4), the mass ratio of the iron salt in the iron salt solution to the porous hollow nitrated microspheres is (3-15):1; And / or, in 4), the iron salt is selected from ferrous sulfate; And / or, in 4), the mass concentration of the ammonia water is 1-35wt%; And / or, in 4), the reaction temperature is 40 to 100°C; And / or, in 4), the reaction time is 1 to 24 hours.
6. The preparation method according to claim 1, characterized in that: The method also includes coating the porous hollow magnetic microspheres, wherein the coating includes the following steps: a first reaction is performed on the porous hollow magnetic microspheres, dibutyltin dilaurate and isophorone diisocyanate, and then hydroxyethyl methacrylate is added for a second reaction to obtain coated microspheres.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the porous hollow magnetic microspheres to the dibutyltin dilaurate is 1:(0.005-0.1); and / or, the mass ratio of the porous hollow magnetic microspheres to isophorone diisocyanate is 1:(0.2-5); And / or, the mass ratio of the porous hollow magnetic microspheres to hydroxyethyl methacrylate is 1:(0.1-1); And / or, the temperature of the first reaction is 40-100°C; And / or, the temperature of the second reaction is 40-100°C; And / or, the method further comprises performing carboxyl modification on the coated spheres, wherein the carboxyl modification comprises the following steps: reacting the coated spheres, azobisisobutyronitrile and acrylic acid.
8. The preparation method according to claim 7, characterized in that: The mass ratio of the coated ball to azobisisobutyronitrile is 1:(0.01-0.5); and / or, the mass ratio of the coated ball to acrylic acid is 1:(1-3); And / or, the reaction temperature is 40-100°C.
9. The porous hollow magnetic microspheres obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the porous hollow magnetic microspheres as claimed in claim 9 for chemiluminescent immunodiagnosis, cell sorting or nucleic acid purification, which does not belong to a method for diagnosing and treating a disease.
Citation Information
Patent Citations
Functional nanometer particle composite non-crosslinking microspheres and preparation method and application thereof
CN102908961A
Monodisperse hollow polystyrene-divinyl benzene composite microsphere, preparation method thereof and application of monodisperse hollow polystyrene-divinyl benzene composite microsphere in enzyme-linked immunosorbent assay
CN115677898A